Conceptual bases of strategy and tactics of audit of financial statements. (Journal of Economic Research & Business Administration, 2016)
With transition to the market relations auditor activity gains the increasing development. In world practice auditor control isn’t an innovation and is widely applied in all fields of activity. In Kazakhstan emergence of the independent control providing needs of users of financial information of economic subjects in the form of confirmation of its reliability is new. Because the confidence in absolute quality of the audit report confirming reliability of the reporting to work of auditor firms and auditors is necessary for users of financial information more and more strict requirements are imposed. Rules (standards) of auditor activity become effective, the system of professional quality control of work of auditors develops, additional requirements are imposed to vocational training from the state. In these conditions auditor firms have to pay more attention to questions of planning of audit, definition of auditor risk, importance of a possible mistake, audit process documenting, development of intra firm standards and techniques of audit.
Keywords: audit; financial statements; asset; passive; capital.